الصحة النفسية لدى مربي الأطفال المعاقين ذهنيا بالمراكز النفسية البيداغوجية - بوساحة، نوال (جامعة الوادي university of eloued, 2018)
"تهدف هذه الدراسة إلى معرفة مستوى الصحة النفسية لدى مربي الأطفال المعاقين ذهنيا بالمراكز النفسية البيداغوجية، ولتحقيق الهدف المرجو أعتمدت الدراسة على المنهج الوصفي الاستكشافي الذي يتناسب مع طبيعة الدراسة. حيث تم تطبيق الدراسة على عينة قدرها (45) مربي أطفال معاقين ذهنيا، عاملين بالمراكز النفسية البيداغوجية الأربعة لولاية الوادي، حيث تم اختيارهم بطريقة مسحية، و تم جمع المعلومات من خلال مقياس الصحة النفسية من إعداد الباحثة، بعد أن تم التحقق من خصائصه السيكومترية ، ومعالجتها وتحليلها بإستخدام ، النسب المئوية ، والمتوسط الحسابي، والانحراف المعياري و إختبار "" ت "" و"" كا2 ""، وقد توصلت الدراسة إلى :  لا يوجد إختلاف في مستوى الصحة النفسية لدى مربي الأطفال المعاقين ذهنيا بالمراكز النفسية البيداغوجية.  توجد فروق ذات دلالة إحصائية للصحة النفسية لدى مربي الأطفال المعاقين ذهنيا بالمراكز النفسية البيداغوجية للأطفال المعاقين ذهنيا تعزى لمتغير جنس المربي.  لا توجد فروق ذات دلالة إحصائية للصحة النفسية لدى مربي الأطفال المعاقين ذهنيا بالمراكز النفسية البيداغوجية للأطفال المعاقين ذهنيا تعزى لمتغير (المستوى التعليمي ،الحالة العائلية، الخبرة المهنية) للمربي. وبناء على النتائج المتحصل عليها من خلال هذه الدراسة يتضح أنه من الضروري توفير بيئة عمل مناسبة تقلل من الضغوط النفسية والاحتراق النفسي لدى المربين، حتى تحفظ لهم صحتهم النفسية وتؤدي إلى تحقيق توازنهم الذاتي من خلال توافقهم الروحي والاجتماعي و الجسمي والعقلي و النفسي . "ملخص الدراسة باللغة الانجليزية: The summary Firstly, this study aimes to o find out the level of mental health among educators of mentally disabled children in psychosocial centers, however, In order to achieve the desired objective, the study relied on the descriptive approach in the exploratory approach that is appropriate to the nature of the study. Secondly, The study was applied to a sample of (45) mentally handicapped children with mental disabilities, working in the four pedagogical centers of Eloued,Where they were selected in a survey, in addition to The data were collected through the mental health measure prepared by the researcher, after checking from psychometric characteristics, then Processing and analysis using percentages, mean arithmetic, standard deviation, and test ""K2 "" & ""T"". The study has reached to: There is no difference in the level of mental health among educators of mentally disabled children in psychosocial centers.  There are statistically significant differences in mental health among educators of mentally disabled children in psychosocial centers of children with mental disabilities according to the gender of the teacher.  There are no statistically significant differences in mental health among educators with mental disabilities in psychosocial centers of children with mental disabilities (education level, family status, professional experience) for teacher . Finally, based on the results obtained through this study it seems that it is necessary to provide an appropriate working environment that reduces the psychological pressure and psychological combustion of educators, so as to preserve their mental health and lead to the achievement of self-harmony and enjoy the adjustment of spiritual, social, physical, mental and psychological.
دراسة وصفية إستكشافية بالمراكز النفسية البيداغوجية لولاية الوادي
مذكرة ماستر في علوم التربية تخصص تأهيل في التربية الخاصة
Keywords: الصحة النفسية، الإعاقة العقلية; Santé mentale, handicap mental; Mental health, mental disability